State-of-the-art global models underestimate impacts from climate extremes - Jacob Schewe (Nature Portfolio, 2019)
Impact models projections are used in integrated assessments of climate change. Here the authors test systematically across many important systems, how well such impact models capture the impacts of extreme climate conditions.